SCREENING OF CLOTTING SYSTEM DISORDERS BY LABORATORY TESTS - A. B. Dobrovolsky; E. V. Titaeva (Российский кардиологический журнал)
The review takes into consideration the diagnostic significance of the main screening coagulologic tests under the light of modern views on the role of vessel wall, plasma proteins and blood cells in the dynamics of thrombin formation and its activities regulation.